Influence of refractive condition on retinal vasculature complexity in younger subjects - Che Azemin, Mohd Zulfaezal; Mohamad Daud, Norsyazwani; Abd Hamid, Fadilah; Zahari, Ilyanoon; Sapuan, Abdul HaliM (Hindawi Publishing Corporation, 2014)
Objective. The aim of this study was to compare the retinal vasculature complexity between emmetropia, and myopia in younger subjects. Methods. A total of 82 patients (24.12 ± 1.25 years) with two types of refractive conditions, myopia and emmetropia were enrolled in this study. Refraction data were converted to spherical equivalent refraction. These retinal images (right eyes) were obtained from NAVIS Lite Image Filing System and the vasculature complexity was measured by fractal dimension (), quantified using a computer software following a standardized protocol. Results. There was a significant difference (< 0.05) in the value of between emmetropic (1.5666 ± 0.0160) and myopic (1.5588 ± 0.0142) groups. A positive correlation (rho = 0.260,